Multidimensional Talent Identification in Taekwondo Kyorugi: Analytical Hierarchy Process (AHP) Method Approach - Fauzi Syahria Zein; Dede Rohmat Nurjaya; Mulyana (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
Taekwondo performance in the modern era has undergone a tactical paradigm shift following the global implementation of the Protector and Scoring System (PSS). In Indonesia, grassroots talent identification remains largely subjective and vulnerable to precociousness bias, indicating the need for objective, multidimensional, and evidence-based selection instruments. This study aimed to develop a comprehensive talent identification model for Taekwondo Kyorugi athletes by determining criteria, sub-criteria, and priority weights using the Analytical Hierarchy Process (AHP). An exploratory sequential mixed-methods design was employed. The qualitative phase involved a systematic literature review to identify relevant talent indicators, while the quantitative phase used an AHP pairwise comparison questionnaire to obtain expert judgments, which were analyzed using Expert Choice software. The participants were 30 experienced Taekwondo coaches from various provinces in Indonesia, all of whom held at least a national coaching license and were actively involved in coaching athletes competing at national and international levels. The AHP results showed that anthropometry was the highest-priority criterion for early talent identification, with a weight of 54.7%, followed by psychology (15.9%), physiology (15.2%), and technical skills (14.2%). At the sub-criteria level, leg length (20.3%) was the most important anthropometric indicator. Speed (5.6%) was the dominant physiological indicator, mental toughness (5.9%) was the leading psychological indicator, and head kick (5.3%) was the highest-priority technical skill. All pairwise comparisons met the consistency requirement, with a Consistency Ratio below 0.10. These findings provide an expert-based priority framework to support more systematic and evidence-based talent identification in Taekwondo Kyorugi.